Tumor Suppressor DAPK1 Catalyzes Adhesion Assembly on Rigid but Anoikis on Soft Matrices - Qin, Ruifang; Melamed, Shay; Yang, Bo; Saxena, Mayur; Sheetz, Michael P.; Wolfenson, Haguy (Frontiers in Cell and Developmental Biology, 2022)
Cancer cells normally grow on soft surfaces due to impaired mechanosensing of the extracellular matrix rigidity. Upon restoration of proper mechanosensing, cancer cells undergo apoptosis on soft surfaces (anoikis) like most normal cells. However, the link between mechanosensing and activation of anoikis is not clear. Here we show that death associated protein kinase 1 (DAPK1), a tumor suppressor that activates cell death, is directly linked to anoikis activation through rigidity sensing. We find that when rigidity sensing is decreased through inhibition of DAPK1 activity, cells are transformed for growth on soft matrices. Further, DAPK1 catalyzes matrix adhesion assembly and is part of adhesions on rigid surfaces. This pathway involves DAPK1 phosphorylation of tropomyosin1.1, the talin1 head domain, and tyrosine phosphorylation of DAPK1 by Src. On soft surfaces, DAPK1 rapidly dissociates from the adhesion complexes and activates apoptosis as catalyzed by PTPN12 activity and talin1 head. Thus, DAPK1 is important for adhesion assembly on rigid surfaces and the activation of anoikis on soft surfaces through its binding to rigidity-sensing modules.